Vital staining with disulfine blue in septic, trauma and restorative bone surgery - Barquet, Antonio (Cirugía del Uruguay, 1982)
In septic, plastic and orthopaedic bone surgery, the precision in the complete resection of necrotic tissues as well as the evaluation of revitalization procedures and the evolutional diagnosis of tissue vitality are absolutely essential in different situations. A very useful procedure in the visual determination of living and devitalized tissue is presented: the vital staining with disulfine blue. The author analyzes its pharmacological basis -emphasizing its nontoxicity-, how practical the procedure is, as well as its uses and indications in this field of surgery.